Factors associated with, and variations in, COVID-19 hospital death rates in England’s first two waves: observational study - Alex Bottle; Paul Aylin; Stephen Brett; Puji Faitna (BMJ Open)
Objectives To assess patient-level and hospital-level predictors of death and variation in death rates following admission for COVID-19 in England’s first two waves after accounting for random variation. To quantify the correlation between hospitals’ first and second wave death rates.Design Observational study using administrative data.Setting Acute non-specialist hospitals in England.Participants All patients admitted with a primary diagnosis of COVID-19.Primary and secondary outcomes In-hospital death.Results Hospital Episode Statistics (HES) data were extracted for all acute hospitals in England for COVID-19 admissions from March 2020 to March 2021. In wave 1 (March to July 2020), there were 74 484 admissions and 21 883 deaths (crude rate 29.4%); in wave 2 (August 2020 to March 2021), there were 165 642 admissions and 36 040 deaths (21.8%). Wave 2 patients were younger, with more hypertension and obesity but lower rates of other comorbidities. Mortality improved for all ages; in wave 2, it peaked in December 2020 at 24.2% (lower than wave 1’s peak) but halved by March 2021. In multiple multilevel modelling combining HES with hospital-level data from Situational Reports, wave 2 and wave 1 variables significantly associated with death were mostly the same. The median odds ratio for wave 1 was just 1.05 and for wave 2 was 1.07. At 99.8% control limits, 3% of hospitals were high and 7% were low funnel plot outliers in wave 1; these figures were 9% and 12% for wave 2. Four hospitals were (low) outliers in both waves. The correlation between hospitals’ adjusted mortality rates between waves was 0.45 (p<0.0001). Length of stay was similar in each wave.Conclusions England’s first two COVID-19 waves were similar regarding predictors and moderate interhospital variation. Despite the challenges, variation in death rates and length of stay between hospitals was modest and might be accounted for by unobserved patient factors.